Case report: Congenital arterioportal fistula: An unusual cause of variceal bleeding in adults - Xia, Junlin; Zhao, Jingwen; Chang, Bing (Frontiers in Medicine, 2022)
The aberrant vascular connecting channel that forms between the portal vein and the hepatic artery is the essence of a hepatic arterioportal fistula. Congenital hepatic arterioportal fistula more frequently occurs in early childhood rather than in adults. We describe a rare instance of a large, isolated, congenital hepatic arterioportal fistula that was successfully treated following selective hepatic arteriography and transcatheter embolization. The patient presented with significant variceal bleeding when the fistula was discovered at the age of 73. The patient's condition improved during the brief postoperative follow-up period without a recurrence. Our research suggests that in older patients with portal hypertension and an unclear etiology, selective arteriography and embolization can provide a definitive diagnosis and successfully treat symptoms.